Tinea capitis caused by Trichophyton tonsurans presenting as an obscure patchy hair loss due to daily antifungal shampoo use - Alita Sombatmaithai (Mattioli1885, 2015)
Tinea capitis is unusual and often misdiagnosed in healthy adults. We report a case of a healthy woman with a several-year history of asymptomatic, bizarre-shaped, non-scarring alopecia. She had used over-the-counter ketoconazole shampoo regularly for a long time. An initial potassium hydroxide preparation showed negative result for fungal organism. The scalp biopsy revealed endothrix infection, and dermoscopic examination demonstrated the comma hair and corkscrew hair signs. The fungal culture showed Trichophyton tonsurans. The daily use of antifungal shampoo could be the important factor to conceal clinical and laboratory findings for diagnosis of T. tonsurans tinea capitis in our case, which required high clinical suspicion and histopathology and dermoscopic examinations.